2010
DOI: 10.4314/sajrs.v32i2.59296
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the recovery-stress, burnout and mood state scores of elite student rugby players

Abstract: A sample of 41 male student rugby players (mean age: 21.87 ± 1.39 years) completed the Recovery-Stress Questionnaire (Kellmann & Kallus, 2001), Athlete Burnout Questionnaire (Raedeke & Smith, 2001) and Stellenbosch Mood Scale (Terry et al., 2003)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
1
10
1
Order By: Relevance
“…Furthermore, Schaufeli and Buunk (2001) observed that within the reactions associated with the burnout syndrome is the variation in mood states. Thus, the results found in the present investigation confirmed that burnout presented a close relationship with changes in mood states, especially with a predisposition to a depressive state (Glass, Mcknight, & Valdimarsdottir, 1993;Grobbelaar, Malan, Steyn, & Ellis, 2010;Leiter & Durup, 1994;Martini, Arfken, Churchill, & Balon, 2004). In addition, since burnout also has been shown to have a negative impact on the physical and psychological wellbeing of athletes and coaches (Raedeke & Smith, 2004), demonstrating the link between burnout and mood states in referees is an important extension for future studies.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, Schaufeli and Buunk (2001) observed that within the reactions associated with the burnout syndrome is the variation in mood states. Thus, the results found in the present investigation confirmed that burnout presented a close relationship with changes in mood states, especially with a predisposition to a depressive state (Glass, Mcknight, & Valdimarsdottir, 1993;Grobbelaar, Malan, Steyn, & Ellis, 2010;Leiter & Durup, 1994;Martini, Arfken, Churchill, & Balon, 2004). In addition, since burnout also has been shown to have a negative impact on the physical and psychological wellbeing of athletes and coaches (Raedeke & Smith, 2004), demonstrating the link between burnout and mood states in referees is an important extension for future studies.…”
Section: Discussionsupporting
confidence: 84%
“…In South Africa a few studies have been done on student burnout and student engagement (Gauché, 2006;Grobbelaar, Malan, Steyn & Ellis, 2010;Grobbelaar, Malan, Steyn & Ellis, 2011;Morgan & De Bruin, 2010;Mostert, Pienaar, Gauché & Jackson, 2007;Pienaar & Sieberhagen, 2005;Strydom, Kuh & Mentz, 2010). However, none of these studies focused on core self-eval uation traits (self-esteem and self-efficacy), career decision-making difficulties or social support as predic tors of student burnout and engagement.…”
Section: Study Contextmentioning
confidence: 97%
“…Factors affecting the recovery-stress, burnout and mood state scores of elite student rugby players 11 .…”
Section: X Xmentioning
confidence: 99%